Dynamic changes in the transcriptome landscape of Arabidopsis thaliana in response to cold stress - Liu, Yue; Cai, Yajun; Li, Yanzhuo; Zhang, Xiaoling; Shi, Nan; Zhao, Jingze; Yang, Hongchun (Frontiers in Plant Science, 2022)
Abstract Plants must reprogram gene expression to adapt constantly changed environmental temperatures. With the increased occurrence of extremely low temperatures, the negative effects on plants, especially on growth and development, from cold stress are becoming more and more serious. In this research, a strand-specific RNA sequencing (ssRNA-seq) was used to explore the dynamic changes in the transcriptome landscape of Arabidopsis thaliana exposed to cold temperatures (4°C) for different periods of time. In total, 7,623 differentially expressed genes (DEGs) exhibited dynamic temporal changes during the cold treatments. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the DEGs were response to cold and involved in secondary metabolic processes, as well as photosynthesis, glucosinolate biosynthesis, and plant hormone signal transduction pathway. Meanwhile, long non-coding RNAs (lncRNAs) were identified after the assembly of the transcripts, from which 247 differentially expressed lncRNAs (DElncRNAs) and their potential target genes were predicted. Alternative splicing (AS) significantly enhanced transcriptome complexity, and 3,621 differentially alternatively spliced (DAS) genes related to RNA splicing and spliceosome were identified. In addition, the expression level of 739 transcription factors (TFs) belonging to 52 gene families were identified. This research analyzed the dynamic changes of the transcriptome landscape in response to cold stress, which reveal a more complete transcriptional patterns during short and long-term cold treatment and provide a new insight into functional studies of how plants are affected by cold stress.